Gender Difference in Renal Blood Flow Response to Angiotensin II Administration after Ischemia/Reperfusion in Rats: The Role of AT2 Receptor - Maryam Maleki; Mehdi Nematbakhsh (Advances in Pharmacological Sciences)
Background. Renal ischemia/reperfusion (I/R) is one of the major causes of kidney failure, and it may interact with renin angiotensin system while angiotensin II (Ang II) type 2 receptor (AT2R) expression is gender dependent. We examined the role of AT2R blockade on vascular response to Ang II after I/R in rats. Methods. Male and female rats were subjected to 30 min renal ischemia followed by reperfusion. Two groups of rats received either vehicle or AT2R antagonist, PD123319. Mean arterial pressure (MAP), and renal blood flow (RBF) responses were assessed during graded Ang II (100, 300, and 1000 ng/kg/min, i.v.) infusion at controlled renal perfusion pressure (RPP). Results. Vehicle or antagonist did not alter MAP, RPP, and RBF levels significantly; however, 30 min after reperfusion, RBF decreased insignificantly in female treated with PD123319 (P=0.07). Ang II reduced RBF and increased renal vascular resistance (RVR) in a dose-related fashion (Pdose<0.0001), and PD123319 intensified the reduction of RBF response in female (Pgroup<0.005), but not in male rats. Conclusion. The impact of the AT2R on vascular responses to Ang II in renal I/R injury appears to be sexually dimorphic. PD123319 infusion promotes these hemodynamic responses in female more than in male rats.